BCZT-BNT-based lead-free composite energy storage ceramic with high breakdown strength and preparation method of BCZT-BNT-based lead-free composite energy storage ceramic

By using BCZT-BNT-based lead-free composite ceramic materials and using traditional high-temperature solid-phase method to prepare, the shortcomings of existing lead-free energy storage ceramic materials in high breakdown strength and high-efficiency energy storage are solved, and the preparation of high-performance energy storage materials is realized to meet the needs of high-power pulse systems.

CN119613108APending Publication Date: 2025-03-14JILIN INST OF CHEM TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411734979.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing lead-free energy-storage ceramic materials are insufficient in terms of high breakdown strength and high-efficiency energy storage, and it is difficult to meet the demand for high-performance energy storage materials of high-power pulse systems.

Method used

BCZT-BNT-based lead-free composite ceramic material is used, and its chemical composition formula is (1-x)[0.25(Bi0.5Na0.5)TiO3-0.75Ba0.85Ca0.15Zr0.1Ti0.9O3]-xBaZrO3, which is prepared by traditional high-temperature solid phase method, with simple process and good repeatability.

Benefits of technology

It achieves high breakdown strength and excellent energy storage characteristics. The breakdown strength of ceramic materials ranges from 600kV/cm to 900kV/cm, and the energy storage efficiency is 88.7% to 90.2%, which is suitable for high-power pulse systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613108A_ABST
    Figure CN119613108A_ABST
Patent Text Reader

Abstract

The invention provides BCZT-BNT-based lead-free composite energy storage ceramic with high breakdown strength and a preparation method of the BCZT-BNT-based lead-free composite energy storage ceramic, and belongs to the field of dielectric energy storage ceramic materials. The general formula of the chemical composition is (1-x) [0.25 (Bi < 0.5 > Na < 0.5 >) TiO < 3 >-0.75 Ba < 0.85 > Ca < 0.15 > Zr < 0.1 > Ti < 0.9 > O < 3 >]-xBaZrO < 3 >, and x is the mole number and ranges from 0.05 to 0.20. According to the preparation method disclosed by the invention, chemical component disorder is induced by doping modification on an atomic scale, and a high-dynamic-polarity nano micro-region (PNRs) is formed, so that the nano micro-region has an obvious dielectric relaxation behavior and a slender ferroelectric hysteresis loop (P-E ring), and the energy storage ceramic material with high energy storage density and energy storage efficiency, ultrahigh breakdown strength and excellent frequency stability is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of dielectric energy storage ceramic materials, and specifically relates to a BCZT-BNT-based lead-free composite energy storage ceramic with high breakdown strength and a preparation method thereof. Background Art

[0002] With the rapid development of electronic information technology and people's increasing awareness of environmental protection, environmentally friendly energy storage materials and devices have become one of the research hotspots in the field of functional materials. Traditional lead-based energy storage ceramic materials, such as lead zirconate titanate (PZT), have excellent piezoelectric properties and energy storage performance, but their high toxicity and high volatility will cause serious pollution to the environment during preparation and use, threatening human health. Therefore, the development of environmentally friendly, high-safety lead-free energy storage ceramic materials has become an urgent need in the field of dielectric capacitors.

[0003] In recent years, sodium bismuth titanate (BNT)-based and calcium barium zirconate titanate (BCZT)-based lead-free ceramic materials have become the research focus in the field of lead-free energy storage ceramics due to their high dielectric constant, excellent piezoelectric properties and potential high energy storage characteristics. In view of the advantages of BNT and BCZT in energy storage performance, the combination of the two to prepare BCZT-BNT-based lead-free composite ceramics is expected to further improve its comprehensive energy storage performance. However, there are currently few research reports on BCZT-BNT-based lead-free composite ceramics, especially in terms of high breakdown strength and efficient energy storage, which requires more research and technological innovation. Summary of the invention

[0004] In view of the problems existing in the prior art, the purpose of the present invention is to provide a BCZT-BNT-based lead-free composite energy storage ceramic with high breakdown strength and a preparation method thereof, so as to solve the problems of low energy storage density and energy storage efficiency of existing lead-free energy storage ceramic materials, thereby meeting the demand of high-power pulse systems for high-performance energy storage materials.

[0005] The present invention first provides a BCZT-BNT-based lead-free composite energy storage ceramic with high breakdown strength, and the general chemical composition formula thereof is:

[0006] (1-x)[0.25(Bi 0.5 Na 0.5 )TiO3-0.75Ba 0.85 Ca 0.15 Zr 0.1 Ti 0.9 O3]-xBaZrO3, where x is the number of moles, ranging from 0.05 to 0.20.

[0007] The present invention provides a method for preparing a BCZT-BNT-based lead-free composite energy storage ceramic with high breakdown strength, comprising the following steps:

[0008] Step 1: According to the chemical formula (1-x)[0.25(Bi 0.5 Na 0.5 )TiO3-0.75Ba 0.85 Ca 0.15 Zr 0.1 Ti 0.9 O3]-xBaZrO3, weigh the initial raw materials of BaCO3, CaCO3, TiO2, ZrO2, Bi2O3 and Na2CO3;

[0009] Step 2: Mix and grind the raw materials weighed in step 1, and then perform a ball milling process on a planetary ball mill using anhydrous ethanol as a ball milling medium, and dry the mixture to obtain a raw material mixture;

[0010] Step 3: pre-calcining the raw material mixture obtained in step 2 to obtain a pre-calcined powder;

[0011] Step 4: The pre-calcined powder obtained in step 3 is subjected to secondary ball milling, mixing, and drying to obtain (1-x)[0.25(Bi 0.5 Na 0.5 )TiO3-0.75Ba 0.85 Ca 0.15 Zr 0.1 Ti 0.9 O3]-xBaZrO3 pre-made powder;

[0012] Step 5: Add an appropriate amount of polyvinyl alcohol binder to the prefabricated powder obtained in step 4, and then press it into a round blank;

[0013] Step 6: Debinding the wafer blank obtained in step 5 to obtain a debinded wafer blank;

[0014] Step 7: The disc blank after debinding in step 6 is sintered at a constant temperature to prepare a BCZT-BNT-based lead-free composite energy storage ceramic material.

[0015] Preferably, the first ball milling time in step 2 is 12 h to 16 h, and the ball milling speed is 230 r / min to 330 r / min.

[0016] Preferably, the drying temperature in step 2 is 100° C. to 120° C., and the drying time is 4 to 6 hours.

[0017] Preferably, the pre-sintering temperature in step 3 is 850° C. to 950° C., the pre-sintering constant temperature time is 3 hours, and the pre-sintering heating rate is 200° C. / h.

[0018] Preferably, the second ball milling time in step 4 is 12 to 16 hours, and the ball milling speed is 230 r / min to 330 r / min.

[0019] Preferably, the drying temperature in step 4 is 100° C. to 120° C., and the drying time is 4 to 6 hours.

[0020] Preferably, the pressing molding conditions in step 5 are 200MPa to 300MPa, and the holding time is 2 to 3min.

[0021] Preferably, the debinding heating rate in step 6 is 100°C / h, the temperature is controlled at 600°C to 800°C, and the temperature is kept at this temperature for 2h.

[0022] Preferably, the sintering temperature in step 7 is 1200° C. to 1300° C., the sintering time is 3 to 5 hours, and the heating rate is controlled to be 100° C. / h.

[0023] Beneficial Effects of the Invention

[0024] 1. The present invention provides a BCZT-BNT-based lead-free composite energy storage ceramic with high breakdown strength and a preparation method thereof. The composition formula of the BCZT-BNT-based energy storage ceramic material is: (1-x)[0.25(Bi 0.5 Na 0.5 )TiO3-0.75Ba 0.85 Ca 0.15 Zr 0.1 Ti 0.9 O3]-xBaZrO3, wherein x=0.05, 0.10, 0.15 and 0.20; the BCZT-BNT-based lead-free composite energy storage ceramic material of the present invention is prepared by a traditional high-temperature solid-phase method, has a simple process, good repeatability, has ultra-high breakdown strength and excellent energy storage characteristics, and is a very potential candidate material for lead-free ceramic dielectric capacitors.

[0025] 2. The BCZT-BNT-based lead-free composite energy storage ceramic material provided by the present invention induces chemical composition disorder through doping modification at the atomic scale to form high dynamic polar nano-microregions (PNRs), which have obvious dielectric relaxation behavior and slender hysteresis loops (PE loops), thereby obtaining energy storage ceramic materials with high energy storage density and efficiency, ultra-high breakdown strength and excellent frequency stability. The breakdown strength of the ceramic sample of the present invention ranges from 600kV / cm to 900kV / cm, and the energy density that can be released reaches 6.248J / cm 3 ~11.1J / cm 3 , the energy storage efficiency is 88.7% to 90.2%.

[0026] 3. The BCZT-BNT-based lead-free composite ceramic of the present invention can be used as an alternative material for high energy storage ceramic-based capacitors and has broad application prospects in pulse power systems. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 XRD spectra of the BCZT-BNT based lead-free composite ceramic materials prepared in Examples 1 to 4.

[0028] Figure 2 The BCZT-BNT-based lead-free composite ceramic materials prepared in Examples 1 to 4 are subjected to a frequency of 10 3 Characteristic curve of dielectric constant changing with temperature at Hz.

[0029] Figure 3 It is a hysteresis loop diagram of the BCZT-BNT based lead-free composite ceramic material prepared in Examples 1 to 4 at the critical breakdown strength.

[0030] Figure 4 This is a hysteresis loop diagram of the BCZT-BNT based lead-free composite ceramic material prepared in Example 3 at different test frequencies. DETAILED DESCRIPTION

[0031] The present invention first provides a BCZT-BNT-based lead-free composite energy storage ceramic with high breakdown strength, and the general chemical composition formula thereof is:

[0032] (1-x)[0.25(Bi 0.5 Na 0.5 )TiO3-0.75Ba 0.85 Ca 0.15 Zr 0.1 Ti 0.9 O3]-xBaZrO3, wherein x is the number of moles, ranging from 0.05 to 0.20; the preferred component x is 0.15, and the ceramic is cubic at room temperature. Figure 1 shown.

[0033] The present invention provides a method for preparing a BCZT-BNT-based lead-free composite energy storage ceramic with high breakdown strength, comprising the following steps:

[0034] Step 1: According to the chemical formula (1-x)[0.25(Bi 0.5 Na 0.5 )TiO3-0.75Ba 0.85 Ca 0.15 Zr 0.1 Ti 0.9 O3]-xBaZrO3 composition, using an electronic analytical balance to accurately weigh the initial raw materials of BaCO3, CaCO3, TiO2, ZrO2, Bi2O3 and Na2CO3 with a purity higher than 99.00% in sequence;

[0035] Step 2: The raw materials weighed in step 1 are mixed and simply ground, and then the raw materials are first ball-milled on a planetary ball mill using anhydrous ethanol as a ball-milling medium, the ball-milling time is preferably controlled to be 12 to 16 hours, and the ball-milling speed is preferably 230 r / min to 330 r / min; preferably, the raw materials are dried at 100° C. to 120° C. for 4 to 6 hours to obtain a raw material mixture;

[0036] Step 3: pre-sintering the raw material mixture obtained in step 2, wherein the pre-sintering temperature is preferably 850° C. to 950° C., the pre-sintering holding time is preferably 3 hours, and the pre-sintering heating rate is preferably 200° C. / h to obtain a pre-sintered powder;

[0037] Step 4: The pre-calcined powder obtained in step 3 is subjected to a second ball milling mixing, the ball milling time is preferably controlled to be 12 to 16 hours, the ball milling speed is preferably 230 r / min to 330 r / min; preferably dried at 100°C to 120°C for 4 to 6 hours to obtain (1-x)[0.25(Bi 0.5 Na 0.5 )TiO3-0.75Ba 0.85 Ca 0.15 Zr 0.1 Ti 0.9 O3]-xBaZrO3 preformed powder;

[0038] Step 5: adding polyvinyl alcohol binder to the preformed powder obtained in step 4 to granulate, and then pressing into a round blank; the mass concentration of the polyvinyl alcohol binder is preferably 8wt%, the pressing conditions are preferably 200MPa-300MPa, and the holding time is 2-3min;

[0039] Step 6: Debinding the blank disc pressed in step 5, preferably controlling the temperature to 600°C to 800°C, holding time to 2h, and controlling the debinding heating rate to 100°C / h;

[0040] Step 7: The disc blank after debinding in step 6 is subjected to constant temperature sintering, wherein the constant temperature sintering temperature is preferably 1200°C to 1300°C, the time is preferably 3 to 5 hours, and the heating rate is controlled to be 100°C / h to prepare a BCZT-BNT-based lead-free composite energy storage ceramic material.

[0041] The present invention is further described in detail below with reference to specific examples, and the raw materials involved in the examples are all commercially available.

[0042] Example 1

[0043] The chemical formula of the BCZT-BNT based energy storage ceramic material of this embodiment is 0.95[0.25(Bi 0.5 Na 0.5 )TiO3-0.75Ba0.85 Ca 0.15 Zr 0.1 Ti 0.9 O3]-0.05BaZrO3, the preparation process includes the following steps:

[0044] According to the stoichiometric ratio, weigh BaCO3 23.2885g, CaCO3 1.9254g, TiO2 12.638g, ZrO2 2.6893g, Bi2O3 4.9799g and Na2CO3 1.1328g, the weighing error is controlled within ±0.0004g; all the weighed raw materials are mixed evenly and poured into a ball mill, and the first ball milling is carried out for a total of 16 hours with anhydrous ethanol as the ball milling medium, and the speed is 330r / min for the first 2 hours, and then the ball milling is carried out for 14 hours at a speed of 230r / min to fully mix the initial raw materials; the slurry after ball milling is dried at 100°C for 4 hours; the dried raw material powder is placed in a muffle furnace for pre-sintering, and the pre-sintering condition is a constant temperature of 850°C for 3 hours; the pre-sintered powder is ball milled for a second time with anhydrous ethanol as the ball milling medium for a total of 12 hours, and the speed is 330r / min for the first 2 hours, and then at 230 r / min speed ball milling for 10 hours; after ball milling, the slurry is dried at 100°C for 4 hours; after drying, 8wt% of polyvinyl alcohol binder is added to granulate the slurry, and then a powder tablet press is used to maintain the pressure for 2 minutes under 300MPa pressure conditions to press into a disc blank with a diameter of ~12mm and a thickness of ~1.5mm; the obtained disc blank is kept at a constant temperature of 600°C for 2h for debinding, and the heating rate is 100°C / h; after debinding, it is buried in a pre-sintered powder of the same composition and sintered into porcelain: the temperature is increased to 1250°C at a heating rate of 100°C / h, and the temperature is maintained for 3h, and then cooled to room temperature with the furnace to prepare a BCZT-BNT-based lead-free composite energy storage ceramic material.

[0045] Example 2

[0046] The chemical formula of the BCZT-BNT based energy storage ceramic material of this embodiment is: 0.90[0.25(Bi 0.5 Na 0.5 )TiO3-0.75Ba 0.85 Ca 0.15 Zr 0.1 Ti 0.9 O3]-0.10BaZrO3, according to the method of Example 1. The difference is that 23.9323g of BaCO3 with a purity higher than 99.00%, 1.8241g of CaCO3, 11.9728g of TiO2, 3.7151g of ZrO2, 4.7178g of Bi2O3 and 1.0731g of Na2CO3 are weighed according to the chemical dosage ratio.

[0047] Example 3

[0048] The chemical formula of the BCZT-BNT based energy storage ceramic material of this embodiment is: 0.85[0.25(Bi 0.5 Na 0.5 )TiO3-0.75Ba 0.85 Ca 0.15 Zr 0.1 Ti 0.9 O3]-0.15BaZrO3, according to the method of Example 1. The difference is that 24.5761g of BaCO3 with a purity higher than 99.00%, 1.72228g of CaCO3, 11.3077g of TiO2, 4.7409g of ZrO2, 4.4557g of Bi2O3 and 1.0135g of Na2CO3 are weighed according to the chemical dosage ratio.

[0049] Example 4

[0050] The chemical formula of the BCZT-BNT based energy storage ceramic material of this embodiment is: 0.80[0.25(Bi 0.5 Na 0.5 )TiO3-0.75Ba 0.85 Ca 0.15 Zr 0.1 Ti 0.9 O3]-0.20BaZrO3, according to the method of Example 1. The difference is that 25.2199g of BaCO3 with a purity higher than 99.00%, 1.6214g of CaCO3, 10.6425g of TiO2, 5.7667g of ZrO2, 4.1936g of Bi2O3 and 0.9539g of Na2CO3 are weighed according to the chemical dosage ratio.

[0051] XRD test was performed on the BCZT-BNT based lead-free composite ceramics prepared in Examples 1 to 4. The test results are as follows: Figure 1 As shown in the figure, all the ceramic samples of each component present a single perovskite phase, and the crystal structure is a pseudo-cubic system. As the doping amount increases, the diffraction peak moves to a lower angle, and the Bragg equation proves that the unit cell volume expands slightly, which is attributed to the larger ionic radius of Ba 2+ and Zr 4+ This is due to the fact that they enter the A site and B site of the BCZT-BNT lattice respectively.

[0052] The BCZT-BNT-based lead-free composite ceramic samples prepared in Examples 1 to 4 were polished to a thickness of 0.8 mm and dried before electrode preparation: First, a 5×5 mm 2 The gold electrode was then silver coated and fired to test the dielectric properties of the sample. Figure 2Show in 10 3 The dependence of the dielectric constant (ε′) of ceramics on temperature (T) at Hz frequency. As the doping content increases, the ε′ platform, which is almost independent of temperature, gradually flattens, which is beneficial to provide dielectric temperature stability of ceramic dielectric capacitors and achieve higher breakdown strength. In particular, the ceramic sample of Example 3 has a higher room temperature dielectric constant ε′ RT ~1260 and better capacitance temperature change rate (TCC), calculated to meet X5R dielectric specifications (-55℃ to 85℃, TCC=(ε'-ε' RT ) / ε' RT ≤±15%)( Figure 2 illustration).

[0053] The BCZT-BNT-based lead-free composite ceramic samples prepared in Examples 1 to 4 were polished to a thickness of 0.1 mm, dried and sputtered with gold electrodes (diameter 2 mm), and then their hysteresis loops (PE loops) were tested at room temperature and a frequency of 10 Hz. The test results are shown in FIG. Figure 3 The breakdown strength and energy storage characteristics of the lead-free composite ceramic material of the above embodiment at room temperature were obtained through data analysis and calculation, and the corresponding results are listed in Table 1.

[0054] Table 1 Breakdown strength and corresponding energy storage characteristics of the BCZT-BNT-based lead-free composite ceramic materials of the above embodiment at room temperature and 10 Hz

[0055]

[0056] The 0.85[0.25(Bi 0.5 Na 0.5 )TiO3-0.75Ba 0.85 Ca 0.15 Zr 0.1 Ti 0.9 The lead-free O3]-0.15BaZrO3 composite ceramic samples were polished to a thickness of ~0.1 mm, dried and sputtered with gold electrodes (diameter ~2 mm). The unipolar hysteresis loops were tested at different frequencies at room temperature and 250 kV / cm. The test frequency range was 10 Hz-500 Hz. The test results are shown in Figure 4 As the measurement frequency increases, the shape of the hysteresis loop remains basically unchanged, which indicates that the energy storage ceramic sample of Example 3 exhibits excellent frequency stability within the test frequency range.

[0057] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A BCZT-BNT-based lead-free composite energy storage ceramic with high breakdown strength, characterized in that: Its chemical composition formula is: (1-x)[0.25(Bi 0.5 Na 0.5 )TiO3-0.75Ba 0.85 Ca 0.15 Zr 0.1 Ti 0.9 O3]-xBaZrO3, where x is the number of moles, ranging from 0.05 to 0.

20.

2. The method for preparing a BCZT-BNT-based lead-free composite energy storage ceramic with high breakdown strength according to claim 1, characterized in that: The steps include: Step 1: According to the chemical formula (1-x)[0.25(Bi 0.5 Na 0.5 )TiO3-0.75Ba 0.85 Ca 0.15 Zr 0.1 Ti 0.9 O3]-xBaZrO3, weigh the initial raw materials of BaCO3, CaCO3, TiO2, ZrO2, Bi2O3 and Na2CO3; Step 2: Mix and grind the raw materials weighed in step 1, and then perform a ball milling process on a planetary ball mill using anhydrous ethanol as a ball milling medium, and dry the mixture to obtain a raw material mixture; Step 3: pre-calcining the raw material mixture obtained in step 2 to obtain a pre-calcined powder; Step 4: The pre-calcined powder obtained in step 3 is subjected to secondary ball milling, mixing, and drying to obtain (1-x)[0.25(Bi 0.5 Na 0.5 )TiO3-0.75Ba 0.85 Ca 0.15 Zr 0.1 Ti 0.9 O3]-xBaZrO3 pre-made powder; Step 5: Add an appropriate amount of polyvinyl alcohol binder to the prefabricated powder obtained in step 4, and then press it into a round blank; Step 6: Debinding the wafer blank obtained in step 5 to obtain a debinded wafer blank; Step 7: The disc blank after debinding in step 6 is sintered at a constant temperature to prepare a BCZT-BNT-based lead-free composite energy storage ceramic material.

3. The method for preparing a BCZT-BNT-based lead-free composite energy storage ceramic with high breakdown strength according to claim 2, characterized in that: The first ball milling time in step 2 is 12h to 16h, and the ball milling speed is 230r / min to 330r / min.

4. The method for preparing a BCZT-BNT-based lead-free composite energy storage ceramic with high breakdown strength according to claim 2, characterized in that: The drying temperature in step 2 is 100° C. to 120° C., and the drying time is 4 to 6 hours.

5. The method for preparing a BCZT-BNT-based lead-free composite energy storage ceramic with high breakdown strength according to claim 2, characterized in that: The pre-sintering temperature in step 3 is 850°C to 950°C, the pre-sintering constant temperature time is 3h, and the pre-sintering heating rate is 200°C / h.

6. The method for preparing a BCZT-BNT-based lead-free composite energy storage ceramic with high breakdown strength according to claim 2, characterized in that: The second ball milling time in step 4 is 12 to 16 hours, and the ball milling speed is 230 r / min to 330 r / min.

7. The method for preparing a BCZT-BNT-based lead-free composite energy storage ceramic with high breakdown strength according to claim 2, characterized in that: The drying temperature in step 4 is 100° C. to 120° C., and the drying time is 4 to 6 hours.

8. The method for preparing a BCZT-BNT-based lead-free composite energy storage ceramic with high breakdown strength according to claim 2, characterized in that: The pressing molding conditions described in step 5 are 200MPa to 300MPa, and the holding time is 2 to 3min.

9. The method for preparing a BCZT-BNT-based lead-free composite energy storage ceramic with high breakdown strength according to claim 2, characterized in that: The debinding heating rate in step 6 is 100°C / h, the temperature is controlled at 600°C to 800°C, and the temperature is kept at this temperature for 2h.

10. The method for preparing a BCZT-BNT-based lead-free composite energy storage ceramic with high breakdown strength according to claim 2, characterized in that: The sintering temperature in step 7 is 1200° C. to 1300° C., the sintering time is 3 to 5 hours, and the heating rate is controlled to be 100° C. / h.

Citation Information

Cited By

  • Preparation method and application of flexible hydroxyl modified BNT-CBZ-OH ceramic particle / polymer composite membrane

    CN120025576A

  • Barium calcium zirconate titanate-sodium bismuth zirconate lead-free piezoelectric ceramic material as well as preparation method and application thereof

    CN120943633A